CFD Based Numerical Analysis of Flow-Field Characteristics on Airfoils Experiencing Transverse Flow - Seidel, C; LeBeau, R; Jayaram, S (International Journal of Computer Sciences and Engineering, 2019)
In the presented work, the flow-field around dropped airfoils was investigated to establish a correlation with transverse flow on a flat plate. This scenario relates to falling maple seeds and developing a fundamental understanding of the how the forces and drag coefficients develop prior to rotation. Understanding the development of these forces will lead to understanding the characteristics of maple seeds (and other auto-rotating seeds) that cause auto-rotation and development of leading-edge vortices. Using CFD, a thin, almost 2D airfoil was placed in a 3D environment and dropped through free space. Flow around the dropped airfoil was accelerated by gravity considerations. The resulting surface forces were evaluated through comparison of coefficient of drag values for transverse flow on a flat plate. The analysis of the forces demonstrated that the drag coefficient values on the lower surface of NACA 0012 and E63 airfoils profile were found to be similar to the flat plate values. The convex NACA 0012 airfoil experienced larger surface forces than flat plate and the concave E63 airfoil experienced smaller surface forces than flat plate. This work also demonstrates that coefficient of drag varies with time.